2015
DOI: 10.3390/s150717495
|View full text |Cite
|
Sign up to set email alerts
|

Low Power Resistive Oxygen Sensor Based on Sonochemical SrTi0.6Fe0.4O2.8 (STFO40)

Abstract: The current paper reports on a sonochemical synthesis method for manufacturing nanostructured (typical grain size of 50 nm) SrTi0.6Fe0.4O2.8 (Sono-STFO40) powder. This powder is characterized using X ray-diffraction (XRD), Mössbauer spectroscopy and Scanning Electron Microscopy (SEM), and results are compared with commercially available SrTi0.4Fe0.6O2.8 (STFO60) powder. In order to manufacture resistive oxygen sensors, both Sono-STFO40 and STFO60 are deposited, by dip-pen nanolithography (DPN) method, on an SO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Our group has considered different approaches [36][37][38][39], and as a result of our investigations we found that ink-jet printing, drop coating and sputtering are the main techniques which satisfy the previously described constrains and are amenable to high volume production at relatively low cost.…”
Section: B Sensing and Nano Materials Integrationmentioning
confidence: 85%
“…Our group has considered different approaches [36][37][38][39], and as a result of our investigations we found that ink-jet printing, drop coating and sputtering are the main techniques which satisfy the previously described constrains and are amenable to high volume production at relatively low cost.…”
Section: B Sensing and Nano Materials Integrationmentioning
confidence: 85%
“…Response time and energy consumption are also topics of research, where the most part of commercial solutions have response times of seconds, sometimes reaching a few minutes; the energy consumption of these devices can reach the order of 500 milliwatts (mW) or even higher, due to the necessity of the heater. As the miniaturization of the devices has shown better response times, of the order of seconds to milliseconds, and power consumption of 80 mW, as reported by the Stratulat et al [124], it has a good potential to be used integrated in an IoT solution. Although no commercial solutions were found employing nanomaterials or microelectromechanical systems (MEMS), this has shown to be a promising technology to future products, allowing the development of embedded systems to measure gas concentrations in diverse scenarios, with lower power consumption than the traditional MOS transducers [125].…”
Section: Metal Oxide Semiconductorsmentioning
confidence: 91%
“…In another report, S. K. Hodak et al [21] have reported ethanol sensing of SrTiO 3 thin films with gas concentration in range of 100 ppme1000 ppm. The oxygen sensing property of SrFe x Ti 1-x O 3 has been proposed via sonochemical method [22]. However, in present investigation, the ethanol sensing of Fe doped SrTiO 3 has been studied for low concentrations (5e50 ppm).…”
Section: Introductionmentioning
confidence: 91%